Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage

3D printing of semicrystalline polypropylene: towards eliminating warpage of printed objects - Bachhar, Nirmalya; Gudadhe, Aniket; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (Bulletin of Materials Science, 2020)
Fused filament fabrication (FFF) is an extrusion-based 3D printing technique for thermoplastic polymers. In this technique, molten polymer is extruded through a print nozzle and is laid down layer by layer to build up the printed object. Currently, FFF is used primarily to print amorphous or low-crystallinity polymers, such as acrylonitrile butadiene styrene copolymer (ABS) or polylactic acid (PLA). Printing of semicrystalline polymers, such as polyethylene or polypropylene remains particularly challenging. During FFF of semicrystalline polymers, large thermomechanical stresses are generated when the polymer solidifies on cooling. These stresses result in warpage of the printed part. Here, we analyse the factors that influence stresses generated during FFF 3D printing of a commercial semicrystalline polymer, isotactic polypropylene. We investigate the effect of height of the printed object on part warpage, as well the effect of infilling during printing. We demonstrate that the stresses generated during FFF can be substantially decreased by incorporation of a `brim', viz. a thin layer at the base of the printed object, and by adhering the brim to the print substrate using common polyvinyl acetate-based glue. We systematically investigate the effect of the brim size on the warpage of the printed object. We support our experimental findings with finite element method (FEM) simulations that explain the mechanism of stress buildup during printing. The trend in stresses calculated in the FEM simulations parallel the warpage measured in the experiments. Thus, this work represents an important methodological advance towards warpage-free FFF printing of semicrystalline polymers.
Keywords: 3D printing; polypropylene printing; warpage

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration